Four arenas of school-based participation: towards a heuristic for children's rights-informed educational practice. Issue 1 (2nd January 2022) - Mannion, Greg; Sowerby, Matthew; I'Anson, John
ABSTRACT: There has been a long-standing call for the participation of young people in decision making in school. However, research to date has mostly focused on pupil councils and is rarely conducted in areas of socio-economic deprivation – the contexts for this study. In national examinations, the schools chosen had higher than average attainments given their catchments. The research sought to understand if and how young people would make a link between their participation rights and 'doing well' at school. Using mobile and visual methods, a situated, social-material approach was taken to data collection and analysis. We found participation opportunities were supportive in four arenas: formal curriculum, wider curriculum, decision making groups, and connections with the wider community. This framing provides a heuristic for rights-based participation in educational practice.